Development of an evaluation instrument for teachers at the College of Allied Medical Professions, University of the Philippines Manila - Santiago, Lorna F. (1999)
This study aimed to develop an instrument for teacher evaluation at the College of Allied Medical Professions (CAMP), UP-Manila. Respondents in the study were CAMP faculty and students. Due to the small number of faculty members, all were included as respondents. Stratified random sampling was utilized to have a good representation of students from the three departments namely the Departments of Occupational Therapy, Physical Therapy and Speech Pathology. A representative sample of 20% from each of the department was used as respondents. A preliminary survey was conducted among the faculty and students to arrive at a list of behaviors which promote effective learning. A list of teacher characteristics was formulated based on the results of the survey, literature review and the old rating scale of the College. This list was then presented to faculty and student respondents through a questionnaire that required them to choose which items are relevant in measuring teaching competency. Relevant items were selected and categorized. The instrument was then presented to the faculty as experts to review its content validity. This was established through a feedback questionnaire that covered the areas of clarity and number of items, sequence and categorizing of items, clarity of directions and appropriateness of the rating scale. Results show that the items in the instrument are valid but several suggestions were given. These suggestions were then considered in the modification of the instrument. The instrument was pilot tested among a 20% student sample from each department to evaluate its inter-rater reliability and practicality. The instrument was found to be practical in terms of length of time of administration. The students were able to accomplish the three page evaluation form at an average of 9 minutes. Determining the average time for administration is important to be able to allot a time limit on future use of the instrument. Percentage agreement among the responses of the raters was determined to establish inter-rater reliability. Results of reliabilities were all above 0.70, which agree with reports of acceptable values of reliability of other researchers. The faculty members at CAMP recognize the need to improve the existing evaluation instrument of the college. The outcome of this study may be used to replace the rating scale currently being used. The instrument will continue to be tested and refined for future use.